Antiproliferative activity of yatein isolated from Austrocedrus chilensis against murine myeloma cells: Cytological studies and chemical investigations. (March 2015) - Donoso-Fierro, César; Tiezzi, Antonio; Ovidi, Elisa; Ceccarelli, Donatella; Triggiani, Doriana; Mastrogiovanni, Fabio; Taddei, Anna Rita; Pérez, Claudia; Becerra, José; Silva, Mario; Passarella, Daniele
Abstract Context: Fitzroya cupressoides (Molina) I. M. Johnst. and Austrocedrus chilensis (D. Don) Pic.Serm. & Bizzarri are two Chilean Cupressaceae that are naturally resistant to biodegradation. Secondary metabolites from these species display a variety of biological activities. Objective: To evaluate the antiproliferative activity of two lignans, a diterpene and a flavonol isolated from A. chilensis and F. cupressoides, to elucidate their cytological effects on P3X murine myeloma cells. Materials and methods: The antiproliferative activity of yatein, isotaxiresinol, ferruginol, and isorhamnetin was evaluated in vitro using the MTT assay. The effect of yatein at the cellular level, due to its high antiproliferative activity was evaluated. P3X cells treated for 24 h with 12.5 and 25 µg/mL of yatein were also examined at the cytological level using immunofluorescence and scanning and transmission electron microscopy. Results: Yatein, a lignan isolated from A. chilensis, potentially inhibited P3X murine myeloma cell proliferation, resulting in approximately 75% cell death in response to a 25 µg/mL treatment with the lignan. P3X cells lost membrane integrity at the nuclear and cytoplasmic levels, including organelles, in response to yatein treatment (12.5 µg/mL), and we observed changes in the cytoplasmic organization and distribution of microtubules. The other compounds tested had low activity. Discussion and conclusions: Yatein is a lignan precursor of podophyllotoxin, a key agent in anticancer drugs. Due to its structural similarities to podophyllotoxin, yatein could have similar cytoplasmic target(s), such as the microtubular apparatus. These findings suggest that yatein may be of potential pharmacological interest and warrants further investigation in human cell lines.